ANALYSIS OF FACTORS AFFECTING BANK SINARMAS LOYALTY TO MILLENNIALS AND GENERATION Z - Joni; Cindy Synthya Br Tarigan; Didik Gunawan; Cici Puspaningrum (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of M-Banking services, customer satisfaction, and location on Bank Sinarmas customer loyalty in the Millennial generation and generation Z. This study uses a quantitative approach to the census method on 172 respondents. This research uses a quantitative approach with a census method of 172 respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results showed that M-Banking services have a significant effect on customer loyalty in both generations. Meanwhile, customer satisfaction does not show a significant influence on loyalty, both in the Millennial generation and the Z generation. The location factor has a significant influence only on generation Z, while in the Millennial generation it is not significant. This indicates that there are differences in preferences between generations on factors that affect loyalty. This research provides important implications for the development of banking service strategies that are oriented towards digital needs and accessibility across generations.